Analisis Yuridis Pengalihan Hak atas Merek Terdaftar berdasarkan Pewarisan (Studi Putusan No. 74/Pdt.Sus-HKI/Merek/2023/Pn Niaga Jkt.Pst) - Vinska Agitha Hasibuan; O.K. Saidin; Tan Kamello (Jurnal Hukum Lex Generalis, 2025)
The transfer of trademark rights through inheritance is a process of transferring inheritance from the testator to the heirs, which can lead to disputes if it does not comply with applicable legal provisions. This normative juridical research uses descriptive analytical methods through library studies to analyze the regulation of registered trademark rights transfer to heirs, legal protection for heirs, and judicial considerations in Court Decision No. 74/Pdt.Sus-HKI/Merek/2023/PN Niaga Jkt.Pst. The research results show that the transfer of trademark rights to heirs is regulated in Article 41 paragraph (1) of Law No. 20 of 2016 concerning Trademarks and Geographical Indications with legal protection that can be carried out preventively and repressively through litigation and non-litigation channels. In the specific case studied, the judge granted the cancellation of the trademark transfer agreement between Bujung Benjamin and Wina Sukamdhani due to proven signature forgery in the agreement made after the testator's death, demonstrating the importance of document authenticity verification in the process of trademark rights transfer through inheritance.